Mechanical properties of ceria-calcia stabilized zirconia ceramics with alumina additions. Issue 11 (September 2021) - Tovar-Vargas, D.; Roitero, E.; Anglada, M.; Jiménez-Piqué, E.; Reveron, H.
Highlights: As a result of grain size reduction, strength and hardness for 10Ce-1CaO and 10Ce-1CaO-5Al2O3 increased compared to 10Ce-TZP. Aging resistance in all 10Ce-1CaO/ alumina composites. Measurement of KI c by SEVNB and VIF methods to corroborate the difference between the values obtained by both methods. Abstract: Ceria-stabilized zirconia-based composites have been developed aiming to obtain ceramic materials with enhanced hardness, strength, fracture toughness, and resistance to low temperature degradation. These composites are based on ceria-calcia stabilized zirconia (10 mol% CeO2 -1 mol% CaO TZP) and α-alumina (0−15 wt%) as a second phase. Raw materials in the form of powders were dispersed through ball milling, dried by slip casting, and subsequently grounded before being pressed and conventionally sintered at 1450 °C. Compared to the strength and hardness of 10Ce-TZP ceramics (typically 500 MPa and 6 GPa), an increase was observed for all compositions, especially for 10Ce-1CaO-5Al2 O3 (739 MPa and 10.2 GPa). Single Edge V-Notched Beam fracture toughness values ranged from 5.1 to 6.6 MPa∙√m, indicating a loss of transformability for all compositions. As in 10Ce-1CaO-TZP co-doped ceramics, the aging resistance of all alumina-containing composites was also excellent.